Association of urinary concentrations of phthalate metabolites with quinolinic acid among women: A potential link to neurological disorders. (May 2020) - Nassan, Feiby L.; Gunn, Joshua A.; Hill, Melissa M.; Williams, Paige L.; Hauser, Russ
Graphical abstract: Highlights: Quinolinic acid (QA) is a neuroactive metabolite. QA is implicated in the pathogenesis of several neurological disorders. Urinary concentrations of several phthalate metabolites were positively associated with QA. This novel finding may partially account for the associations of phthalate exposures with neurodevelopmental disorders. Abstract: Background: Quinolinic acid (QA), a neuroactive metabolite produced during tryptophan degradation, is implicated in the pathogenesis of several neurological disorders. Phthalates are structurally similar to QA, and exposure to phthalates has demonstrated increased QA production and excretion in rodent studies. We recently showed that very high exposure to dibutyl phthalate was associated with higher concentrations of urinary QA in men. However, no human studies examined the associations between background (low) phthalate exposures and QA. Objectives: To examine the associations of urinary concentrations of phthalate metabolites with QA. Methods: Female participants (N = 126) who participated in a prospective cohort study at the Massachusetts General Hospital Fertility Center provided 758 urine samples (273 during pregnancy and 485 during non-pregnancy). Concentrations of 11 phthalate metabolites and QA in urine were measured. We used multivariable linear mixed effect models to estimate the percent change in urinary QA concentrations associated with a doubling (100%) of urinary phthalate metabolite concentration, and evaluated whether there was effect modification by pregnancy status. Results: Women's mean (standard deviation) age was 34.2 (4.0) years with a body mass index of 23.5 (3.7) kg/m 2 . The women were primarily Caucasian (92%), had at least a college degree (98%), and none were current smokers. Pairwise Spearman correlations between concentrations for phthalate metabolites and QA measured in the same urine samples ranged from 0.36 for MEHP to 0.68 for dibutyl phthalate (DBP) metabolites. In multivariable-adjusted models, the percent change in urinary QA concentrations was significantly higher for each doubling of several urinary phthalate metabolite concentrations. For example, each doubling of DBP metabolites was associated with a 13.7% (95%CI: 10.6, 16.9)% higher QA. Associations between the low molecular weight phthalate metabolites and QA were stronger among samples collected during pregnancy as compared to non-pregnancy samples from the same women. Conclusions: Urinary concentrations of several phthalate metabolites were positively associated with QA among women. These findings, along with the known neurotoxicity of QA, warrant the need to examine whether QA concentrations may serve as a pathway for the adverse neurodevelopment outcomes found in children's health studies.